Analysis of KCl and H2SO4 Electrolyte Concentration Variations on Specific Capacitance of Electrodes (CNT/PVA) Through Cyclic Voltammetry (CV) - Reza, Mutia; Lusi Ernawati; Asful Hariyadi; Ranti Kusuma Wardhani; Thalia Winda Sari; Novi Sylvia (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Escalating need for power usage is the author’s concern in producing this research. Supercapacitors are one of the energy storage devices that have better performance than conventional capacitors. Supercapacitor components generally consist of electrodes, electrolytes, and separators. Electrolytes have an important role that can affect the specific capacitance of supercapacitors. This research resulted in analyzing the type and variation of electrolyte concentrations in the form of KCl and H2SO4 at concentrations of 0.4; 0.7 and 1 M, respectively. Cyclic voltammetry (CV) was conducted using carbon nanotube electrodes which were molded into sheets using Polyvinyl Alcohol (PVA) binder. CV analysis aims to determine the supercapacitor performance as measured by the specific capacitance value. Based on the observation of the results obtained, the best specific capacitance in each type of electrolyte KCl and H2SO4 at a concentration of 1 molar is 55.561 and 54.981 F/g, respectively.